Religions view religions : explorations in pursuit of understanding - Gort, Jerald D.; Jansen, Henry; Vroom, H. M., 1945-2014 (Currents of encounter, 2006)
Because religion is so central to the lives and experience of the vast majority of people throughout the world, it figures very prominently in a variety of ways in interhuman relations. Unfortunately, 'religion' often appears to be one of the potent sources of mistrust, discord and strife between and among individuals, groups and cultures. What frequently lies at the root of such suspicion and dissension is general ignorance concerning the religious other, a lack of knowledge about his or her beliefs, aspirations and views of the good and morally honorable life. And even if people have some fa.